Analisis Persepsi Kebermanfaatan, Kemudahan Penggunaan dan Kepercayaan terhadap Minat Penggunaan Financial Teknologi Sebagai Layanan Pembayaran Digital - Mariyatul Qibtiyana; Hapzi Ali (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
In the digital era, the primary focus is on the use of fintech as a payment tool. This research delves into the factors influencing fintech adoption within the financial sector, primarily focusing on perceived usefulness, ease of use, and trust in the technology. Highlighting these factors, the study demonstrates their impact on user interest in adopting fintech. The research methodology involves data collection from literature reviews and observations. Fintech is regulated by financial authorities and offers transactional convenience. The research concludes that the success of fintech adoption strongly correlates with perceived usefulness, ease of use, and trust. Positive perceptions regarding the benefits and user-friendliness of fintech drive its adoption, providing a foundation for fintech companies to enhance their services